(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This study investigates the standardization of quality control and documentation processes for locally grown medicinal herbs in Bangladesh, focusing on enhancing their export potential. Despite Bangladesh’s rich biodiversity and a longstanding tradition of using medicinal plants, the export of these herbs is hindered by inconsistent quality and inadequate documentation. Our findings revealed that most producers and collectors have educational qualifications below the Secondary School Certificate (SSC) level and do not adhere to formal guidelines. Key issues identified include a lack of proper documentation practices such as record keeping, accurate labelling, and appropriate packaging. This research highlights the critical need for targeted training and education initiatives to improve adherence to Good Agricultural and Collection Practices (GACP). The study aims to align local practices with international standards by developing a framework that addresses these gaps, ensuring that exported herbs meet global market requirements. The findings are expected to contribute significantly to the sustainable development of Bangladesh’s herbal industry and its successful integration into the global market. Dhaka Univ. J. Pharm. Sci. 24(1): 49-66, 2025 (June)